Disulfide cross-linked cholic-acid modified PEG–poly(amino acid) block copolymer micelles for controlled drug delivery of doxorubicin1. Issue 38 (30th April 2015) - Li, Yuling; Shen, Yuling; Wang, Sai; Zhu, Dandan; Du, Baixiang; Jiang, Jihong
<x xml:space="preserve">Abstract</x> Reduction responsive biodegradable core-cross-linked micelles are developed form lipoic acid and cholic acid decorated poly(ethylene glycol)-b-poly(l-glutamic acid) block copolymers and investigated for intracellular doxorubicin release.